Patient-centered group psychotherapy for depression and negative emotions: a systematic review and meta-analysis - Yang-yang Yin; Zhen-zhen Wan; Bo Wang (Frontiers in Psychiatry)
ObjectiveDepressive disorders and negative emotions are a major global health challenge, affecting over 280 million people and worsened by the COVID-19 pandemic. Traditional treatments have limitations such as high relapse rates and accessibility issues. This study aimed to assess the efficacy of patient-centered group psychotherapy (PCGP) on depressive symptoms and functional outcomes, identify moderators, and provide recommendations.MethodsFollowing PRISMA guidelines, we searched PubMed, CNKI, and other databases through October 2024, including 7 randomized controlled trials (RCTs) and one Clinical study (total N = 1,989). Study quality was assessed using the Newcastle-Ottawa Scale. Random-effects meta-analyses via RevMan 5.4 calculated risk ratios (RRs) and standardized mean differences (SMDs), with heterogeneity evaluated via I² statistics.ResultsEligible participants comprised adults (≥18 years) with a principal diagnosis of major depressive disorder (DSM-5/ICD-10 criteria) or clinically significant negative emotional symptoms (e.g., PHQ-9≥15), excluding those with primary non-depressive psychiatric comorbidities. Studies involving mixed populations were included only if subgroup data for depressed participants were extractable. PCGP showed significant positive effects on overall effectiveness (RR = 1.10, 95% CI: 1.01-1.19, p = 0.03), symptom reduction (Positive and Negative Syndrome Scale (PANSS) scores, SMD = -1.96, 95% CI: -2.31 to -1.61, p < 0.001), and functional outcomes (Personal and Social Performance (PSP) scores, SMD = 1.96, 95% CI: 1.41-2.51, p < 0.001). It also improved negative mood (SMD = -4.28, 95% CI: -8.03 to -0.52, p = 0.03) but with high heterogeneity (I² = 99.0%). A positive trend was noted for medication adherence (RR = 1.11, 95% CI: 0.89-1.38, p = 0.35).ConclusionPCGP is an effective first-line adjunct therapy for depression, particularly in resource-limited settings. It addresses both symptom reduction and functional recovery by combining personalized goal-setting with group dynamics.